Prevalence of Work-Related Musculoskeletal Disorders among Physical Educators of Hyderabad, Pakistan - Hanan Bukhari Syed; Khadijatul Ain Sandeela; Rida Mustafa Khan (The Sky, 2024)
Physical education is a comprehensive approach that involves educating the individuals through physical activity to improve the social, cognitive as well as physical skills. Physical education teachers undergo higher level of occupational physical activities and repetitive movements and are more prone to develop sports injuries and Work-Related Musculoskeletal Disorders. The aim of the study is to identify the prevalence of work-related musculoskeletal disorders among physical education teachers of Hyderabad. This study is a cross sectional observational survey. 100 participants were recruited from different institutes of Hyderabad. Data were collected by Nordic musculoskeletal questionnaire and data were analyzed by SPSS software version 21.0. The results show that the prevalence of work-related musculoskeletal disorders among physical educators are highest level in case of lower back pain (42%) followed by shoulder (36%) and neck (28%). This study concludes that occupational musculoskeletal disorders are highly prevalent among physical education teachers of Hyderabad. Low back pain and shoulder discomfort has also been more commonly reported among the respondents.